2014
DOI: 10.1242/dmm.014969
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish reporter lines reveal in vivo signaling pathway activities involved in pancreatic cancer

Abstract: Pancreatic adenocarcinoma, one of the worst malignancies of the exocrine pancreas, is a solid tumor with increasing incidence and mortality in industrialized countries. This condition is usually driven by oncogenic KRAS point mutations and evolves into a highly aggressive metastatic carcinoma due to secondary gene mutations and unbalanced expression of genes involved in the specific signaling pathways. To examine in vivo the effects of KRASG12D during pancreatic cancer progression and time correlation with can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 75 publications
1
30
0
Order By: Relevance
“…Previous studies have shown increased expression of TGF-β ligands as well as progressive activation of TGF-β signaling during pancreatic cancer progression. 18,20,33 Indeed, we observed gradual increase of Tgfb1 expression in KC pancreas in the time course (Figure 6b). Interestingly, at 1 and 3 months of age, Tgfb1, Tgfb2 and Tgfbr2 expressions in LKC pancreas were higher than those in KC pancreas.…”
Section: Notch Activation Antagonizes Tgf-β Signaling In the Mouse Pamentioning
confidence: 72%
“…Previous studies have shown increased expression of TGF-β ligands as well as progressive activation of TGF-β signaling during pancreatic cancer progression. 18,20,33 Indeed, we observed gradual increase of Tgfb1 expression in KC pancreas in the time course (Figure 6b). Interestingly, at 1 and 3 months of age, Tgfb1, Tgfb2 and Tgfbr2 expressions in LKC pancreas were higher than those in KC pancreas.…”
Section: Notch Activation Antagonizes Tgf-β Signaling In the Mouse Pamentioning
confidence: 72%
“…For example, butylparaben‐induced cell dispersion has also been shown in rodent models; Alam et al found butylparaben to cause the collapse of rat Sertoli cell vimentin filaments, allowing spermatogenic cells to separate from the Sertoli cells (Alam & Kurohmaru, ). Vimentin filaments are found in pancreatic precursor cells and in beta‐cell neogenesis, (Ko et al, ), and an increase is a marker of pancreatic cancer progression in zebrafish (Schiavone et al, ). Studies are under‐way to determine whether vimentin disruption contributes to the aberrant beta cell architecture in the developing islet.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the generation and use of zebrafish transgenic and mutant lines may provide new opportunities to better understand the biology of NB and to test in vivo potential chemical tumor suppressors through high-throughput drug screening. In addition, zebrafish models of NB crossed with cell signaling reporter fish might be a powerful tool for the in vivo dissection of the signaling cascades and molecular mechanisms involved in tumor development [96, 97]. …”
Section: Discussionmentioning
confidence: 99%